2021
DOI: 10.1155/2021/6593293
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics, Rheological Properties, and Antioxidant Activity of Novel Polysaccharides from “Deer Tripe Mushroom”

Abstract: The polysaccharide was extracted by water extraction and alcohol precipitation method from “deer tripe mushroom,” which was domesticated and bred from wild Auricularia delicata in Zambia. The structure of the deer tripe mushroom polysaccharide (DTMP) was characterized by gas chromatography-mass spectrometry (GC-MS), Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance spectroscopy (NMR), scanning electron microscope (SEM), and other analytical techniques. And the rheological and gel prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…When the concentrations of different sample solutions were 0.1, 0.3, and 0.5%, respectively, G ’ and G ” values of CSFP suggested no cross-linking, while cross-formation occurred and the gel formation and elastic properties of CSFP1-β and CSFP2-α increased with increasing concentrations. Hu et al ( 61 ) extracted polysaccharide (DTMP) from “deer tripe mushroom” and studied its rheological and gel properties. The results indicated that the DTMP solution showed shear-thinning behavior (pseudoplasticity), and its pseudoplasticity was more obvious at a concentration of 2%.…”
Section: Resultsmentioning
confidence: 99%
“…When the concentrations of different sample solutions were 0.1, 0.3, and 0.5%, respectively, G ’ and G ” values of CSFP suggested no cross-linking, while cross-formation occurred and the gel formation and elastic properties of CSFP1-β and CSFP2-α increased with increasing concentrations. Hu et al ( 61 ) extracted polysaccharide (DTMP) from “deer tripe mushroom” and studied its rheological and gel properties. The results indicated that the DTMP solution showed shear-thinning behavior (pseudoplasticity), and its pseudoplasticity was more obvious at a concentration of 2%.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it could potentially be effective in the role of preventive agents in combatting the pathogenesis of certain diseases [ 117 ]. Furthermore, it has been demonstrated that polysaccharides derived from deer tripe mushrooms ( A. delicata ) possess radical scavenging action [ 118 ]. The results from the DPPH and ABTS assays were relatively good but not comparable to vitamin C [ 118 ].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Furthermore, it has been demonstrated that polysaccharides derived from deer tripe mushrooms ( A. delicata ) possess radical scavenging action [ 118 ]. The results from the DPPH and ABTS assays were relatively good but not comparable to vitamin C [ 118 ]. The study found that the crude polysaccharide has strong antioxidant properties, with a clear dose-effect relationship at lower concentrations [ 118 ].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has found that ADe extracts showed antimicrobial, hepatoprotective, and antioxidant effects [ 25 ]. Polysaccharides from ADe effectively scavenged -OH and O 2 - in vitro, indicating its antioxidant properties [ 27 ]. However, few studies have examined the regulatory effects of ADe on obesity and elucidated its underlying mechanisms [ 25 ].…”
Section: Introductionmentioning
confidence: 99%